2018
DOI: 10.1017/wet.2018.98
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Formulation and Rate on Rice Tolerance to Early-Season Applications of Acetochlor

Abstract: Acetochlor (WSSA Group 15) is a very-long-chain fatty acid–inhibiting herbicide used to control grass weed species in row crops and could potentially be effective when used in a rice herbicide program. A field study was conducted in 2016 and 2017 at four locations to determine the effects of acetochlor formulation and rate on rice tolerance. Overall, rice was more tolerant to the microencapsulated (ME) formulation of acetochlor than to the emulsifiable concentrate (EC) formulation, likely because of the potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 21 publications
1
18
0
1
Order By: Relevance
“…Rice tolerance to acetochlor, butachlor, oxadiazon, pretilachlor, and thiobencarb is consistent with previous reports (Fogleman et al 2018;Kirkwood and Fletcher 1984;Wilson et al 2014). In the present study, however, substantial rice damage on both rice varieties was observed with anilofos and clomazone.…”
Section: Resultssupporting
confidence: 91%
“…Rice tolerance to acetochlor, butachlor, oxadiazon, pretilachlor, and thiobencarb is consistent with previous reports (Fogleman et al 2018;Kirkwood and Fletcher 1984;Wilson et al 2014). In the present study, however, substantial rice damage on both rice varieties was observed with anilofos and clomazone.…”
Section: Resultssupporting
confidence: 91%
“…Furthermore, the formulation of acetochlor can influence crop safety and weed control efficacy. Fogleman et al (2018) found 48% injury to rice at 2 WAA from the EC formulation, while injury from the CS formulation was only 22%. The CS formulation is a polymer coated product that slowly releases acetochlor over time which provides longer residual weed control and improved crop safety (Cahoon et al, 2015;Fogleman et al, 2018;Li et al, 2008;Rao, 2000).…”
Section: Introductionmentioning
confidence: 94%
“…At Pine Tree and Stuttgart in 2019, when compared to all other treatments, the treatment containing pendimethalin þ thiobencarb applied DPRE followed by two sequential EPOST applications of acetochlor followed by benzobicyclon postflood was much more injurious (≥41%) to the rice when evaluated at 14 d after the postflood application (Table 7). Previous research indicated that when a single microencapsulated acetochlor application was made EPOST, rice injury was tolerable (Fogleman et al 2019); however, when an emulsifiable concentrate formulation of acetochlor was applied, rice injury was not tolerable. Therefore the microencapsulated formulation of acetochlor was chosen for use in this research.…”
Section: Rice Injurymentioning
confidence: 99%